Use of Enrofloxacin in Calcium Beads for Local Infection Therapy in Animals - Pareeya Udomkusonsri,; Santi Kaewmokul,; Surapong Arthitvong,; Taveesak Songserm, (Agriculture and Natural Resources, 2010)
Antibiotic-loaded beads have been used widely for the treatment of local bacterial infections, but many bacterial pathogens have become resistant to antimicrobial agents. Various antibiotic beads were prepared and studied for their efficacy to treat bacterial infections, using the elution profiles of enrofloxacin from calcium sulfate beads in vitro. The beads were prepared by mixing 1.0 g enrofloxacin and 10.0 g calcium sulfate. The beads were placed in phosphate buffer (pH 7.4) for 20 d and eluted enrofloxacin concentrations were determined by agar diffusion microbioassay. The study showed that calcium sulfate beads released enrofloxacin at rates that were higher than the minimal inhibitory concentration (MIC) throughout the 20-day period, with the rate of enrofloxacin release being rapid early in the period. The cumulative eluted enrofloxacin after 20 d was 8.08±0.92% (mean±standard deviation). It was concluded that enrofloxacin-loaded calcium sulfate beads provided a possible treatment for local infections in veterinary medicine. In addition, the calcium beads were simple to prepare, were effective carriers and had antibacterial properties.